The Impact of Governance, Corruption Control, and Political Stability on Economic Growth in Nepal: An Econometric Analysis - Poudel, Omkar; Khatri, Bishnu Bahadur; Acharya, Pradeep (Journal of Political Science, 2025)
This research investigates the impact of governance quality, political stability, corruption management, regulatory quality, and governmental effectiveness on economic growth in Nepal, utilizing annual time series data spanning from 1996 to 2022. Advanced econometric techniques, including Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Canonical Cointegrating Regression (CCR), are employed to analyze both short- and long-term relationships. The results reveal a significant positive relationship between political stability and economic growth (FMOLS coefficient = 5.51E+09, p < 0.01), underscoring the importance of a stable political environment. Conversely, government effectiveness negatively correlates with GDP (FMOLS coefficient = -2.31E+10, p < 0.01), suggesting potential inefficiencies in governance. Corruption control exhibits mixed effects, showing a positive influence on GDP in some models (CCR coefficient = 1.11E+10, p < 0.10). Similarly, regulatory quality yields variable results, with a positive DOLS coefficient of 9.68E+09 (p < 0.05). Johansen's cointegration test confirms significant long-term relationships among the variables, while Granger causality tests identify political stability and government effectiveness as key drivers of GDP. These findings highlight the need for governance reforms that focus on enhancing political stability, improving regulatory quality, and addressing inefficiencies in public administration. Policymakers are urged to implement targeted strategies to promote sustainable economic growth in Nepal.